2020
DOI: 10.1164/rccm.202002-0359le
|View full text |Cite
|
Sign up to set email alerts
|

Reply to Decroo et al.: High-Dose First-Line Treatment Regimen for Recurrent Rifampicin-Susceptible Tuberculosis

Abstract: GenoType MTBDRplus. rpoB mutations outside the 81-bp rifampicin resistance determining region are not covered by these commercial assays. Another, not unusual cause of missed rifampicin resistance is heteroresistance resulting from a mixed population of both susceptible and resistant TB bacilli (3). If patients with resistance to isoniazid and missed rifampicin resistance were treated with the World Health Organization levofloxacin-strengthened first-line regimen, resistance to fluoroquinolone would emerge rap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…As noted for other drugs discussed in this practice guideline, QT interval prolongation may occur with delamanid use, and routine ECG monitoring is recommended. A recent evaluation of the cardiac safety of delamanid and bedaquiline given together as part of multidrug therapy for MDR-TB concluded that the combined effect on the corrected QT interval (QTc) using the Fridericia formula (QTcF) is clinically modest and no more than additive (ClinicalTrials.gov Identifier: NCT02583048), with mean change in QTcF from baseline at 11.9 milliseconds (95.1% CI, 7.4–16.5 ms) in the bedaquiline arm, 8.6 milliseconds (95.1% CI, 4.0–13.2 ms) in the delamanid arm, and 20.7 milliseconds (95.1% CI, 16.1–25.4 ms) in the combined bedaquiline and delamanid arm (136).…”
Section: Drugs and Drug Classesmentioning
confidence: 99%
“…As noted for other drugs discussed in this practice guideline, QT interval prolongation may occur with delamanid use, and routine ECG monitoring is recommended. A recent evaluation of the cardiac safety of delamanid and bedaquiline given together as part of multidrug therapy for MDR-TB concluded that the combined effect on the corrected QT interval (QTc) using the Fridericia formula (QTcF) is clinically modest and no more than additive (ClinicalTrials.gov Identifier: NCT02583048), with mean change in QTcF from baseline at 11.9 milliseconds (95.1% CI, 7.4–16.5 ms) in the bedaquiline arm, 8.6 milliseconds (95.1% CI, 4.0–13.2 ms) in the delamanid arm, and 20.7 milliseconds (95.1% CI, 16.1–25.4 ms) in the combined bedaquiline and delamanid arm (136).…”
Section: Drugs and Drug Classesmentioning
confidence: 99%